URGENSI PAI DALAM PEMBENTUKAN KEDISIPLINAN SISWA DI SMP IT BALIKPAPAN ISLAMIC SCHOOL - Rini, Hardiyanti; Yusuf, Iskandar (Sindoro: Cendikia Pendidikan, 2025)
This study aims to see the urgency of PAI in the formation of student discipline at SMP IT Balikpapan Islamic School. This study uses a qualitative descriptive approach with data collection techniques in the form of observation, interviews, and documentation. The results of the study are 1. Islamic Religious Education has a very strategic role in forming the character and discipline of students at SMPITM BIS. PAI not only provides an understanding of religious values, but also instills moral principles that are an important foundation for the formation of a disciplined attitude. 2. The main challenge we face in implementing PAI to improve the discipline of grade VII students is the difference in background and parenting patterns that students have. 3. The role model of teachers and school staff is a key factor in forming student discipline. Students tend to imitate the behavior they see, not just what they hear. 4. The most effective method is an integrative approach, where PAI values ​​are not only taught in theory in class, but also practiced in various school activities. For example, through the tahsin, tahfidz, congregational prayer, and character building programs. Another approach we use is habituation, such as giving rewards and punishments that are in accordance with Islamic values. In addition, a personal approach is also very important, namely by building a good relationship between teachers and students so that students feel appreciated and more open to receiving advice. 5. Collaboration between schools and parents is very important in instilling student discipline. We always hold regular communication with parents through forums such as parenting day, parent-teacher meetings, and class communication groups. One of our flagship programs is "Mutabaah yaumiyah" where parents are asked to monitor students' daily worship at home, such as obligatory prayers, reading the Qur'an, and helping with homework. With the synergy between schools and parents, the formation of character and student discipline can be carried out consistently both at school and at home. Penelitian ini bertujuan untuk melihat urgensi pai dalam pembentukan kedisiplinan siswa di SMP IT Balikpapan Islamic School. Penelitian ini menggunakan pendekatan deskriptif kualitatif dengan teknik pengumpulan data berupa observasi, wawancara, dan dokumentasi. Hasil dari penelitian adalah 1. Pendidikan Agama Islam memiliki peran yang sangat strategis dalam membentuk karakter dan kedisiplinan siswa di SMPITM BIS. PAI bukan hanya memberikan pemahaman tentang nilai-nilai keagamaan, tetapi juga menanamkan prinsip-prinsip moral yang menjadi landasan penting bagi pembentukan sikap disiplin. 2. Tantangan utama yang kami hadapi dalam menerapkan PAI untuk meningkatkan kedisiplinan siswa kelas VII adalah perbedaan latar belakang dan pola asuh yang dimiliki siswa. 3. Keteladanan guru dan staf sekolah adalah faktor kunci dalam membentuk kedisiplinan siswa. Siswa cenderung mencontoh perilaku yang mereka lihat, bukan hanya yang mereka dengar. 4. Metode yang paling efektif adalah pendekatan integratif, di mana nilai-nilai PAI tidak hanya diajarkan secara teori di kelas, tetapi juga dipraktikkan dalam berbagai aktivitas sekolah. Misalnya, melalui program tahsin, tahfidz, shalat berjamaah, dan character building. Pendekatan lain yang kami gunakan adalah pembiasaan, seperti memberikan reward dan punishment yang sesuai dengan nilai-nilai Islami. Selain itu, pendekatan personal juga sangat penting, yaitu dengan membangun hubungan yang baik antara guru dan siswa sehingga siswa merasa dihargai dan lebih terbuka untuk menerima nasihat.5. Kolaborasi antara sekolah dan orang tua sangat penting dalam menanamkan kedisiplinan siswa. Kami selalu mengadakan komunikasi rutin dengan orang tua melalui forum seperti parenting day, rapat wali murid, dan grup komunikasi kelas. Salah satu program unggulan kami adalah "Mutabaah yaumiyah" di mana orang tua diminta untuk memantau ibadah harian siswa di rumah, seperti shalat wajib, membaca Al-Qur'an, dan membantu pekerjaan rumah. Dengan adanya sinergi antara sekolah dan orang tua, pembentukan karakter dan kedisiplinan siswa dapat dilakukan secara konsisten baik di sekolah maupun di rumah.